REVIEW: A skilful weaving of Teaiwa’s creative legacy - Anaïs Duong-Pedica (Pacific Journalism Review, 2022)
Sweat and Salt Water: Selected Works: Teresia Kieuea Teaiwa, compiled and edited by Katerina Teaiwa, April K. Henderson and Terence Wesley-Smith. Pacific Islands Monograph Series. Honolulu: University of Hawai'i Press. 2021, 286 words. ISBN 9780824890285.